CONTROL OF GENE ACTIVITIES IN THE POLYTENE CHROMOSOMES OF Chironomus tentans BY ECDYSONE AND JUVENILE HORMONE - Lezzi, Markus (1969)
The injection of ecdysone (molting hormone) into chironomid larvae is known to result in the stimulation of specific gene activities (increased RNA synthesis). The morphological manifestation of this gene activation is the formation of a puff. Cytological and autoradiographic analysis of several regions of the salivary gland chromosomes of Chironomus tentans revealed that ecdysone also stimulates Balbiani ring 1. In contradistinction to the puffs, the Balbiani rings are tissue specific and account for a significant percentage of the cell's non-nucleolar RNA. The application of juvenile hormone results in a decreased activity of Balbiani ring 1, suggesting that the two hormones may act antagonistically. In addition, juvenile hormone induces a puff at chromosome region I-19-A and this puff becomes less active after a short-term treatment with ecdysone. These data demonstrate an effect of juvenile hormone on puffing and are the first to demonstrate activation of a Balbiani ring by ecdysone.